ENGAGEMENT KARYAWAN GENERASI Z (STRATEGI UNTUK MENINGKATKAN PRODUKTIVITAS) - Firdya Febriyanti; Mauludia MP; Saepudin Saepudin; Calvin Ananda H.P; Agus Wahyudi (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The purpose of this journal research is to identify effective strategies for enhancing employee engagement among Generation Z to boost workplace productivity. In the era of Generation Z, who grew up in the digital age, they possess unique characteristics that can influence their work behavior and expectations towards the work environment. This study employs a quantitative method through surveys conducted with 200 Generation Z employees across various industries. The research findings indicate that factors such as work flexibility, recognition of contributions, and opportunities for personal development significantly affect their engagement levels. Strategies such as implementing technology that supports collaboration, continuous training programs, and an inclusive company culture have proven to enhance employee productivity. The implications of this research provide practical guidance for managers in designing more targeted engagement programs to improve the performance and loyalty of Generation Z employees.